Mahar Broh in Acehnese Singkil Marriage: Perspectives on Customary Law and Islamic Law - Siregar, Ali Muktar; ananda, Faisar; Yazid, Imam (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This study aims to find out the dowry law in fuqaha studies. Knowing the provisions of Mahar Broh in the marriage of the Acehnese Singkil community. As well as to know the law of dowry broh according to Islamic law. This research uses qualitative type research methods with an ethnographic approach, to try to reveal and study a phenomenon in the Aceh Singkil region. This study used observational data collection techniques, interviews and documentation. This research data analysis technique uses data reduction, data presentation and data verification / conclusions. The results of this study show that (1) Fuqaha has agreed that dowry is a condition of validity for marriage  and no consent should be made to abolish it, Islamic Law has stipulated that the giving of dowry from a husband to his wife is mandatory in marriage. The size of the dowry is not limited. The dowry can be one thousand or a billion, but it can also be one hundred or fifty thousand rupiah, it can even be with a ring made of iron as long as the prospective wife likes and sincerely accepts it. (2) The provision of dowry with a dowry in the form of a dowry in the form of goods (gold) for which payment is suspended, there must be a guarantee in the form of a piece of land equal to the agreed amount of dowry. And the male party must pay off the dowry before the specified time limit, when the dowry is not paid then automatically the broh becomes the full property of the wife. (3) The giving of dowry in the marriage of the Aceh Singkil community can be a legal basis through several things, the dowry must be repaid before the promised time passes, A piece of land that is broh as a guarantee for dowry must be equivalent to the amount of dowry mentioned when contracting, only in the area of Aceh Singkil Regency because the community continues to preserve this culture. and legally Islam is better off going back to the Qur'an and Hadith